Resurgence : towards a responsive urbanism the architectural re - adaptation of marginal space : Pretoria CBD - Barker, A.A.J. (Arthur Adrian Johnson) (University of Pretoria, 2016)
Mini Dissertation (MArch(Prof))--University of Pretoria, 2015.